Production of 64Cu and 67Cu with accelerator neutrons by deuterons and their separation from zinc - Nagai, Yasuki; Kawabata, Masako; Saeki, Hideya; Motoishi, Shoji; Hashimoto, Kazuyuki; Tsukada, Kazuaki; Motomura, Arata; Ohta, Akio; Takashima, Naoki; Hashimoto, Shintaro; Itoh, Masatoshi; Kikunaga, Hidetoshi; et al. (Frontiers in Nuclear Medicine, 2025)
The 64Cu/67Cu pair is an ideal set of theranostic radionuclides for treating patients based on their genetic profiles. We propose a novel production route for this radionuclide pair using accelerator-generated neutrons. We report experimental measurements of the absolute activity and radionuclide purity of 64Cu and 67Cu, produced by irradiating 64Zn and 68Zn with these neutrons. The measured results were consistent with simulated values. 64Cu and 67Cu were separated from the irradiated natural Zn and 68Zn using sublimation and column separation techniques. The production methods for 64Cu and 67Cu developed in this study are expected to enhance their availability in an economically sustainable manner.